UPAYA MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) DENGAN MODEL QUANTUM TEACHING DI KELAS V SEKOLAH DASAR - Hutari .; Mardiana .; Suryansyah . (STKIP Melawi, 2015)
Abstract: The purpose of this study is to increase students' interest in thesubject of Natural Science. The method used in this research wasClassroom Action Research (CAR) by using learning Quantum TeachingModel. The result of the research showed increases in students’ interest inthe subject of Natural Sciences on each cycle. From the results obtainedonthe pre cycle, students who were interested in studying Natural Scienceamounted to 2 students, and on cycle I, the number of students who tookan interest in studying Natural Science is 4 students, whileon cycle II, thefigure of the students who were interested in studying Natural Science is 6students.Keywords: student interest, natural science learning (ipa), quantumteaching model.Abstrak : Tujuan Penelitian ini adalah untuk meningkatkan minat belajarsiswa terhadap mata pelajaran Ilmu Pengetahuan Alam (IPA). Metodedalam penelitian ini ialah Penelitian Tindakan Kelas (PTK) denganmenggunakan pembelajaran Model Quantum Teaching. Hasil Penelitianadanya minat belajar siswa pada mata pelajaran Ilmu Pengetahuan Alam(IPA) dalam setiap siklusnya, dari hasil yang didapat terlihat dalam prasiklus, siswa yang berminat belajar mata pelajaran Ilmu PengetahuanAlam (IPA) berjumlah 2 siswa, pada siklus I, siswa yang berminat belajarmata pelajaran Ilmu Pengetahuan Alam (IPA) berjumlah 4 siswa, danpada siklus II, siswa yang berminat belajar mata pelajaran IlmuPengetahuan Alam (IPA) berjumlah 6 siswa.Kata Kunci: minat belajar siswa, pembelajaran ilmu pengetahuan alam(IPA), model quantum teaching.